Child-Marriage: Knowledge, Parent-Child Communication In Kubu Raya, Kalimantan Barat - Charisma, Putri Anisa; Hayati, Risna; Filya, Rizki (Al-Qalb : Jurnal Psikologi Islam, 2024)
Knowledge is needed to filter social media’s information so social media users are not plunged into risky action. Therefore, reasoning skills are needed to prevent this action. One of the risky actions is promiscuity, which can lead to child-marriage. Child marriage is a serious issue, especially in West Kalimantan, as the province with the fourth highest rate of child-marriage in Indonesia. The role of parent-child communication is essential in the psychological development of adolescents in order to provide proper attention for them. Parent-child communication needs to have an understanding to find out the effect and factors of child-marriage. This study explores the contribution of knowledge and parent-child communication related to child-marriage. Using a qualitative approach, this study was analyzed with qualitative descriptive design. The respondents were 10 parents with children who decided to have a child-marriage. The study indicates that parent-child communication is limited to small talk, not related to the substance of preventing child-marriage. Some parents rarely even communicate with their children. The lack of communication is due to lack of access to education from both parents and teenagers. Respondents are unaware of the impacts or risks they would experience from the decision to marry their children. This happened because most of respondents' education was only limited to elementary school and some even dropped out of school.